SEMANTIC-GRAMMATICAL AND METHODOLOGICAL FEATURES OF ENGLISH PHRASEOLOGY - Guzalkhon, Khaydarova; Nafisa, Kakharova; Maftunakhon, Kodirova; Barchinoy, Eralieva (International Journal of Psychosocial Rehabilitation, 2020)
The article covers the dialectic of generality and specificity of English phraseology in the language and speech stages, phraseological units in separate areas, and their semantic-grammatical and methodological features in the functional methods of speech, especially the semantic, grammatical and emotional-expressive features of professional phraseological units. The article also provides an in-depth analysis of the object of study of phraseological units, the attitude to the stages of formation and development of phraseological units.